“Green” particle technology: Its history, successes, and open issues - Peukert, Wolfgang; Bück, Andreas (Powder Technology, 2024)
We present thoughts on the development of particle technology in the contexts of climate change and circular economy. We begin with a brief outline of the history of particle technology. In addition to the fascination of particle technology, it will become clear that dispersed phases have also been associated with negative consequences of human activity since the industrial revolution and still are. We then discuss some examples of how fine particle systems contributed to solving current technical issues. Finally, we identify some white areas and open questions of particle technology in the context of climate change in the hope of stimulating further research.
CRIS-Team Scopus Importer:2024-09-20
Keywords: Particle technology; Particles; Sustainability